An evaluation of the fourth grade students' English curriculum in Saudi Arabia - Aljuhaish, Sultan Fahd (Kulliyyah of Education, International Islamic University Malaysia, 2015)
The teaching of English language in the Kingdom of Saudi Arabia (KSA) has witnessed substantial development through the past decades. This present work evaluates perceptions among teachers who taught English with the curriculum of the fourth grade primary students in the KSA. The curriculum was prepared by the Ministry of Education with the aim to promote and improve the basic language skills among students of 10 to 11 years old. Four study objectives were set to undergo evaluation: (i) The perceptions of teachers on the content of the fourth grade English curriculum, against the objectives set by the Ministry of Education in the KSA(ii) teachers' perceptions on the content of the fourth grade English curriculum (iii) teachers' perceptions of the effectiveness of curriculum materials and methods of teaching the fourth grade English curriculum in the KSA (iv) the extent to which the newly implemented fourth grade English curriculum in the KSA met the needs and expectations of the teachers. The study utilized the Context, Input, Process and Product (CIPP) Evaluation Model and the evaluative questionnaires were distributed to all 145 teachers from the various participating schools. It was found practicable to analyse the perceptions of 140 teachers directly using quantitative approach; while the qualitative method was applied taking only the purposeful sampling technique and involving five respondents. Results from both approaches revealed that the fourth grade English curriculum seemed not to fulfill the objectives set by the Ministry of Education. A large discrepancy between the targeted age and the curriculum appears to have emerged. Respondents viewed that although the curriculum is well designed, yet it is not suitable for fourth grade pupils. Some respondents (84.1%) highlighted that the curriculum is useable in the daily life of learners while some disagreed with this assertion. The study concludes that there is a need to consider the theoretical age difference between targeted learners and the curriculum-level, and moreover to add topics that can promote students' critical and creative thinking.